Association between endothelin-1, nitric oxide, and Gensini score in chronic coronary syndrome - Yujin Wang; Yuqin Wang; Tiaoxia Liu; Yifan Qin; Futian Tang; Xiaowei Zhang; Yongnan Li (BMC Cardiovascular Disorders, 2023)
Abstract Background Chronic coronary syndrome (CCS) is a major public health burden; its pathogenesis involves atherosclerosis and endothelial dysfunction. Endothelin-1 (ET-1) and nitric oxide (NO) are vasoactive substances synthesized by endothelial cells that play a crucial role in CCS development. The Gensini score (GS) is used for evaluating CCS severity based on lumen segment changes, stenosis degree, and coronary stenosis site. Methods This prospective study included 71 patients with CCS; we evaluated the relationships between GS and ET-1 and NO serum levels were evaluated in these patients. The GS was calculated for all patients. Serum ET-1 & NO levels among other laboratory parameters were measured. Results The high GS group had higher ET-1 and relatively NO expressions in the than the low GS group. GS was positively correlated with ET-1 and negatively correlated with NO, T4, and TSH levels. The results of the multiple linear regression analysis showed that ET-1 had the most significant effect on GS. Conclusions We found a strong association between ET-1, NO, and CCS severity. A combination of ET-1, NO, and GS is an essential predictor of CCS disease severity.